The Effectiveness of the CIRC Learning Model in terms of Self Confidence and Mathematical Generalization Ability - Budi Cahyono; Rina Dwi Setyawati; Alicia Indah Ardiani; Dyan Falasifa Tsani; Budi Waluyo; Kartono Kartono (International Conference on Science, Education, and Technology, 2022)
Abstrak. This study aims to find out that the Cooperative Integrated Reading and Composition (CIRC) learning model is effective against self-confindence and mathematical generalist abilities of students in the material and ranks of class X TKJ SMK Mutiara Mayong. The population in this study were all students of class X TKJ SMK Mutiara Mayong. The sample of this study was class X TKJ 2 and X TKJ 3 which were randomly selected from three classes, each of which had 27, 18 and 23 students. The instrument used to collect data was a mathematical generalization ability test in the form of 5 problem descriptions and a self-confidence questionnaire consisting of 38 questions. Testing the effectiveness of Cooperative Integrated Reading and Composition (CIRC) learning models is carried out with a one sample t-test to determine whether there is an increase in students' generalization and self-confidence abilities between experimental classes before and after treatment is given. Meanwhile, to test whether there are differences in mathematical generalization abilities and students' self-confidence between the experimental class and the control class, a t-independent test is performed. The results showed that (1) effective Cooperative Integrated Reading and Composition (CIRC) learning model in terms of students 'self-confidence, (2) Cooperative Integrated Reading and Composition (CIRC) learning model effectively in terms of students' generalization abilities.